Family firm culture’s influence on socioemotional wealth and financial performance in single-family-owned food processing firms - Galinoma Lubawa; Saganga Mussa Kapaya (African Business Management Journal)
While family business studies on socioemotional wealth and family-owned firms’ financial performance are growing globally, most have focused on European, Asian and American family firms, where economic and cultural changes have altered traditional family structures. These prior studies have predominantly examined private family-owned firms with diverse ownership structures, with limited attention paid to single-family-owned firms. Therefore, to address the identified research gap, this study analysed 267 Tanzanian single-family-owned food processing firms to assess the influence of family firm culture on socioemotional wealth and firms’ financial performance using generalised structural equation modelling. The study’s findings indicate that family firm culture significantly influenced the socioemotional wealth dimensions of family continuity, family prominence and family enrichment, positively affecting firms’ financial performance. This study recommends that family business owners prioritise family firm culture in their socioemotional wealth and financial performance strategies. The study suggests that future research should develop qualitative instruments for measuring socioemotional wealth dimensions.